Decorin Expression and Oncosuppression in Human Embryonic Carcinomas - Sainio, Annele; Pennanen, Mirka; Laine, Jukka; Lund, Riikka; Soderstrom, Mirva; Kuopio, Teijo; Jarvelainen, Hannu (Archives of Clinical and Medical Case Reports, 2019)
Human embryonic stem cells in culture can transform into malignant, cancer-like cells exhibiting lesser differentiation. After transplantation, these transformed cells can form highly malignant germ cell tumors. In humans, germ cell tumors often appear at gonadal sites, like in the testis. In this study, we examined the expression of small leucine rich proteoglycans in normal and karyotypically abnormal human embryonic stem cells using a publicly available transcriptome data. We also examined the expression of the small leucine rich proteoglycans in healthy human testis and in different human testicular non-seminoma germ cell tumors using IST Online database. Furthermore, we localized the expression of decorin, the prototype member of the small leucine rich proteoglycans, in samples representing the above testicular tissues, using in situ hybridization and immunohistochemistry. The analysis revealed that the expression of two small leucine rich proteoglycans, namely decorin and lumican, was induced in normal but not in karyotypically abnormal human embryonic stem cells during early cell differentiation. Similarly, in IST Online database the expression of these two small leucine rich proteoglycans was markedly higher in differentiated teratoma tissue than in undifferentiated embryonal carcinoma tissue. In testicular germ cell tumors decorin expression was completely lacking in the areas of undifferentiated malignant cells. The above results collectively suggest that decorin and lumican have a role in human stem cell differentiation and testicular non-seminoma germ cell tumor formation.